Research Trends and Focus on the Deserts of Northern China: A Bibliometric Analysis During 1986–2020 - Shi, Ya-Fei; Huang, Fang-Fang; Shi, Shan-Heng; Jiang, Ying-Sha; Huang, Xiao-Min (Frontiers in Earth Science, 2021)
With the economic progress and scientific development since the 1980s, research on deserts in China has advanced remarkably. Many research outputs have been published, especially in recent years. However, a systematic review and quantitative analysis of these publications has been lacking. Here, we conducted a comprehensive bibliometric analysis of the main deserts in China in order to characterize the trends and temporal changes in publications. Because the first publication was found in 1986, we searched all publications from 1986 to 2020. We found that annual publication output increased exponentially, especially after 2012, and that the Tengger Desert, the Taklimakan Desert, and the Horqin Sandy Land were the most intensively studied areas. Earth science, involving environmental science and ecology, geology, and agriculture were the major research fields. In addition, Journal of Arid Land, Chinese Science Bulletin, and Catena were the journals with the largest number of publications. The Chinese Academy of Sciences produced the largest number of publications, wherein, Li X R, Zhao X Y, and Zhang Y M were the three most productive authors. Noticeably, “climate change” has become a frequent topic since 2010, indicating that more attention has been paid to climate change and alleviating anthropogenic disturbances in desert areas in China. Although Chinese authors contributed the most publications, the average number of citations per publication for Chinese authors was relatively low. Our results highlight that authors should continue to improve the number of citations of their publications and pay more attention to the interactions between climate change and desertification in the deserts research of Northern China in the futures.